DETERMINASI PENGAMBILAN KEPUTUSAN ETIS AUDITOR INTERNAL (Studi Empiris pada BUMN dan BUMD di Magelang dan Temanggung) - Abdurrahman, Abdurrahman; Laila Yuliani, Nur (Widya Warta, 2011)
Internal auditors play important roles in an organization concerning management, accounting, and operational functions. The multiple roles played by internal auditors include those as professionals and as members of organization in which they often bring internal auditors into auditing conflicts potential to generate ethics dilemma. This research aims to test empirically ethical decision-making processes done by internal auditors related to ethics orientation, professional commitment, job experience, and independency. The sample of this research was taken by the use of purposive sampling method. The number of the sample is 38 internal auditors of BUMN and BUMD in Magelang and Temanggung, who have done at least two auditings. The data analysis was conducted using descriptive statistic test, data quality test which consisted of validity test and reliability test. While, hypothesis test applied doubled linear regression, t test, and F test. The result of the analysis indicates that (1) ethics orientation, professional commitment, and independency partially had positive influence toward ethical decision making by internal auditors with significance level of ethics orientation 0,014, professional commitment 0,026, and independency 0,020 (2) ethics orientation, professional commitment, job experience, and independency simultaneously had positive influence with significance value 0,000 (3) there was not significant influence between job experience and ethical decision making by internal auditors.